Knowledge and value : a new perspective on corporate transformation - Wikström, Solveig. (Routledge, 1994)
The company and the importance of knowledge. The knowledge concept. Changing business. Towards a value-creating partner system. Redefining the market relationship. Organizing for knowledge. Integrated production. The company as a knowledge system.